2018
DOI: 10.1016/j.cortex.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subject-case marking on agreement processing: ERP evidence from Basque

Abstract: Previous cross-linguistic research has found that comprehenders are immediately sensitive to various kinds of agreement violations across languages. We focused on Basque, a verb-final ergative language with both subject-verb (S-V) and object-verb (O-V) agreement. We compared the effects of S-V agreement violations on comprehenders' event-related brain potentials (ERPs) in transitive sentences (where O-V agreement is present, and the subject is ergative) and intransitive sentences (where O-V agreement is abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Thus, since we used a 750 ms stimulus onset asynchrony, participants had 1800 ms to extract person information from the subject before encountering the verb ( la viuda a menudo VERB ). This time interval should have allowed participants to generate predictions (e.g., Chow et al, 2018b). Alternatively, the semantic features of lexical DPs might have impacted processing at the verb, either by allowing the parser to predict the type of event encoded by the verb, or by allowing combinatorial processing with the verb’s semantic features (even if the verb itself was not predicted).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, since we used a 750 ms stimulus onset asynchrony, participants had 1800 ms to extract person information from the subject before encountering the verb ( la viuda a menudo VERB ). This time interval should have allowed participants to generate predictions (e.g., Chow et al, 2018b). Alternatively, the semantic features of lexical DPs might have impacted processing at the verb, either by allowing the parser to predict the type of event encoded by the verb, or by allowing combinatorial processing with the verb’s semantic features (even if the verb itself was not predicted).…”
Section: Discussionmentioning
confidence: 99%
“…The adverb a menudo “often” intervened between the subject and verb in order to create some linear distance between the agreeing elements. We reasoned that this might give the parser a better opportunity to engage in predictive processing, since additional time is available for prediction generation (e.g., Chow et al, 2016, 2018b). Thus, if subject–verb agreement is ever predictive, we thought that this would be an appropriate set-up to explore such a possibility.…”
Section: Methodsmentioning
confidence: 99%
“…Levin (1983) was the first to discover this correlation between case morphology and argument structure, showing that the class of unaccusative predicates in this language correlates with absolutive-marked subjects, whereas the class of unergatives has ergativemarked subjects (see also Laka 1993 for a discussion). Since unaccusative subjects do not have the same case as other subjects, Levin speculated that there might be no syntactic movement for unaccusative subjects in Basque, but refrained from claiming it because it violated the principle in Government and Binding that case could not be determined by D-Structure representations (Chomsky 1981). More recently, Laka (2006a, b;2017) has shown that this correlation is strict, and has argued that case is inherent in Basque, not structural.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the UH makes two claims: (i) there are two different types of argument structure involved in intransitive predicates, one has an agent as the sole argument of the verb and the other one has a theme as the sole argument of the verb (unaccusatives) and (ii) the syntactic derivation of unaccusatives involves one more step than that of unergatives, namely the promotion of the theme argument from object to subject. Burzio (1986) rephrased this second claim in the UH in the framework of Government and Binding (Chomsky 1981) in terms of syntactic movement: the theme argument of an unaccusative verb is generated as its complement and then moves to subject position, whereas the agent argument of an unergative verb is generated as an external argument. Bever & Sanz (1997) were the first to experimentally test the UH; they conducted a reaction time study in Spanish to explore whether the trace left by the argument of unaccusative verbs in the complement of V position, argued to be an anaphor (Chomsky 1981), would prime semantically related nouns as overt anaphors do.…”
mentioning
confidence: 99%
See 1 more Smart Citation